2022
DOI: 10.3389/fmolb.2022.977122
|View full text |Cite
|
Sign up to set email alerts
|

Role of USP13 in physiology and diseases

Abstract: Ubiquitin specific protease (USP)-13 is a deubiquitinase that removes ubiquitin from substrates to prevent protein degradation by the proteasome. Currently, the roles of USP13 in physiology and pathology have been reported. In physiology, USP13 is highly associated with cell cycle regulation, DNA damage repair, myoblast differentiation, quality control of the endoplasmic reticulum, and autophagy. In pathology, it has been reported that USP13 is important in the pathogenesis of infection, inflammation, idiopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 122 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…Knockdown of USP13 accelerated lung fibroblasts phenotypic changes and contributed to pulmonary fibrosis. 29,30 USP13 loss facilitated susceptibility to bleomycin-induced lung fibrosis in vivo model. 50 USP13 expression was up-regulated in lung fibroblasts, and USP13 deficient decreased ECM expression (collagen, SMA, and fibronectin).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Knockdown of USP13 accelerated lung fibroblasts phenotypic changes and contributed to pulmonary fibrosis. 29,30 USP13 loss facilitated susceptibility to bleomycin-induced lung fibrosis in vivo model. 50 USP13 expression was up-regulated in lung fibroblasts, and USP13 deficient decreased ECM expression (collagen, SMA, and fibronectin).…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have shown that USP13 exerted important functions in modulating lung fibrosis and ECM deposition. Knockdown of USP13 accelerated lung fibroblasts phenotypic changes and contributed to pulmonary fibrosis 29,30 . USP13 loss facilitated susceptibility to bleomycin‐induced lung fibrosis in vivo model 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…USP13 has been known to participate in the pathogenesis of infection, cancers, inflammation and neurodegenerative diseases (115). For example, USP13 inhibited lung inflammation via stabilization of the anti-inflammatory receptor IL-1R8/single immunoglobin interleukin-1-related receptor (Sigirr) (116).…”
Section: Usp13mentioning
confidence: 99%